Ranking the world : grading states as a tool of global governance - Cooley, Alexander, 1972-; Snyder, Jack L. (Cambridge : Cambridge University Press, 2015)
Over the last decade, international rankings have emerged as a critical tool used by international actors engaged in global governance. State practices and performance are now judged by a number of high-profile indices, including assessments of their levels of corruption, quality of democracy, creditworthiness, media freedom, and business environment. However, these rankings always carry value judgments, methodological choices, and implicit political agendas. This volume expertly addresses the important analytical, normative, and policy issues associated with the contemporary practice of'grading states'. The chapters explore how rankings affect our perceptions of state performance, how states react to being ranked, why some rankings exert more global influence than others, and how states have come to strategize and respond to these public judgments. The book also critically examines how treating state rankings like popular consumer choice indices may actually lead policymakers to internalize questionable normative assumptions and lead to poorer, not improved, public policy outcomes.
Machine generated contents note: 1. The emerging politics of international rankings and ratings: a framework for analysis Alexander Cooley; 2. Just who put you in charge? We did: CRAs and the politics of ratings Rawi Abdelal and Mark Blyth; 3. Corruption rankings: constructing and contesting the global anti-corruption agenda Mlada Bukovansky; 4. Measuring stateness, ranking political orders: indexes of state fragility and state failure Nehal Bhuta; 5. Competing measures of democracy in the former Soviet Republics Seva Gunitsky; 6. Winning the rankings game: the Republic of Georgia, USAID, and the Doing Business project Sam Schueth; 7. Conclusion. Rating the ratings craze: from consumer choice to public policy outcomes Jack Snyder and Alexander Cooley.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Nation-state and globalization; International relations -- Statistics -- Political aspects; International economic relations -- Statistics -- Political aspects; World politics -- 21st century